Studi of Morfometric Measurement and Phisiological Status in Hawksbill Turtles (Eretmochelys imbricata) - Muhammad Ardiansyah Nurdin; Amelia Ramadhani Ansar; Zulfikar Basrul; Septiadi Yusuf Sulaiman; Nabilla Azzah Jamil; Rozalinda Rozalinda; Nur Azisya (Hasanuddin University, 2022)
Hawksbill turtle ( Eretmochelys imbricata ) is one of the protected fauna because of its endangered population and belongs to the family Cheloniidae. Hawksbill turtle population in Indonesia continues to decline. The decline in its population in nature is caused mainly by human factors ( egg theft , hunting, habitat degradation and extraction of marine natural resources that are used as food for turtles) and health problems when compared to natural factors and predators. There are very few studies on the health of the hawksbill turtle, even though the data and information are very much needed in efforts to save the hawksbill. Basic data needed to determine animal health, including body morphometric and physiological information in the form of body temperature values, heart rate and respiration. This study aims to obtain basic morphometric data and body physiology of the body's work system in hawksbill turtles as initial data in determining health abnormalities of hawksbill turtles. This study used 2 hawksbill turtles obtained in the waters of Bulukumba Regency. Morphometric measurements of the body were carried out after the hawksbill turtle was successfully loaded onto the research boat and measured using a flexible roll meter. Measurement of physiological status was carried out using auscultation and inspection techniques on the plastron and dorsal neck while body temperature measurements were carried out on the cloaca. The results showed that the morphometric measurements and physiological status of the hawksbill turtle had a mean result of BL being 73.5 cm, CCL was 58.5cm, SCL was 57 cm, CCW was 51.5 cm, SCW was 48.5 cm, PL was 44.5 cm, PW was 46 cm. , BC is 84.5 cm, TEM is 25.9°C, Hr is 40.5x/min, and RES is 44x/min. These results indicate that there are differences in morphometric values ​​and physiological status of the wild hawksbill turtle obtained from the waters of Bulukumba Regency . Keywords : Bulukumba, Eretmochelys imbricata, Morphometric, Wild Hawksbill Turtle, Physiological status